A Faculty Development Session or Resident as Teacher Session for Clinical and Clinical Teaching Techniques; Part 2 of 2: Engaging Learners with Effective Clinical Teaching - Megan Boysen-Osborn; Margaret Wolff; Michael Gisondi (eScholarship Publishing, University of California, 2016)
Audience: This workshop is intended for faculty members in an emergency medicine (or other) residency program, but is also appropriate for chief residents and medical student clerkship educators. Introduction: Faculty development sessions are required by the Accreditation Council for Graduate Medical Education and enhance the learning environment within residency programs. Resident as teacher sessions are important in helping residents transition from junior learners to supervisors of medical students and junior residents. Part I of this two-part workshop introduces learners to effective techniques to engaging learners with clinical and bedside teaching. Objectives: By the end of this workshop, the learner will: 1) describe and implement nine new clinical teaching techniques; 2) implement clinical teaching techniques specific to junior and senior resident learners. Methods: This educational session is uses several blended instructional methods, including team- based learning (modified), the flipped classroom, audience response systems, pause procedures.